Bicubic B-Spline And Thin Plate Spline On Surface Appoximation - Liew, Khang Jie (2017)
In real life, the available data points which are either 2D or 3D are normally scattered and contaminated with noise. The noise is defined as the variation in a set of data points. To fit these data points, the approximation methods are considered as a suitable mean compared to the interpolation methods. It is important for the approximation methods to preserve the shape and features of the model in the presence of any noise. B-spline and thin plate spline approximation are being studied in this thesis. The effectiveness of the modified B-spline approximation algorithm is investigated in approximating the bicubic B-spline surface from the samples of scattered data points taken from the point set model.